(untitled) - Vaughan, Duncan A. (Manila, Philippines, 1994)
This handbook contains sections on the following topics: the relationship between Oryza and other grasses; species relationships within the genus Oryza; the nomenclature of Oryza species; the evaluation and uses of wild rices; use of wild rices for evaluation, breeding or experimental purposes; choosing wild rice germplasm for evaluation and plant breeding; sources of wild rice seeds, their germination and culture; and areas of future endeavor. Details are also given of each of 22 wild species including information on morphology, habitat and distribution.
Keywords: Oryza,Oryza; dentification,Germplasm resources